Assessment of the alcohol consumption among outdoor bar drinkers in Nigeria by qualitative methods - Victor O. Lasebikan; Olatunde Ayinde; Mayokun Odunleye (BMC, 2018)
Abstract Background There are indications that drinking in outdoor bars, such as at motor-parks, by the roadsides or street corners have become popular in Nigeria. Method Three sets of qualitative assessments were carried out from three outdoor bars, randomly selected from 22 of such in Ibadan, Nigeria. The main sources of data were by direct observation and focus group discussion (FGD), conducted by a non-probabilistic sample of outdoor bar drinkers, alcohol vendors and from community members. The qualitative assessments were recorded, followed by a thematic analysis of the contents of the qualitative assessments. Results Widespread use of alcohol was reported. Patrons of outdoor bars reported that their context of drinking was pleasurable to them. Use of local beverages usually called 'sepe' is increasing. The majority of them do not have adequate health information about the harmful consequences of alcohol. Alcohol and other substances of abuse were openly displayed, sold and consumed at the study sites. There were poor law provision and enforcement of laws prohibiting open display of alcohol and other substances. Conclusion A high proportion of social drinkers in outdoor bars require intervention for their drinking behaviour. This is important because they have little or no information about the health hazards associated with excessive drinking. Presentation of these findings should contribute to increased awareness and improved response from the policy makers.